Increasing Learning Outcomes of Students with Hearing Impairment Using Powerpoint as Teaching Media in Explaining the Concept of Animal Life Cycle - K Kurniawati (Indonesian Journal of Community and Special Needs Education, 2022)
The purpose of this study was to determine the improvement of science learning outcomes on the subject of animal life cycles through the use of Powerpoint media for students with hearing impairment. the method used is classroom action research using demonstration learning methods, giving assignments, and asking questions. The subjects of this study were 4  students with hearing impairment at the Sekolah Luar Biasa Negeri Bekasi Jaya, Indonesia. The results showed that student learning outcomes have increased so that it exceeds the Minimum Completeness Criteria that have been set, namely 80. This happens because the Powerpoint media used is easily understood by students. This study demonstrates that the use of Powerpoint media is easy to understand and attracts students' attention, thereby accelerating students' understanding, especially deaf students, about the life cycle of animals. In addition, Powerpoint media will also make it easier for teachers to guide students, especially for students with hearing impairment.